2017
DOI: 10.1002/ccd.27427
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of early mechanical circulatory support in acute myocardial infarction complicated by cardiogenic shock: The Detroit cardiogenic shock initiative

Abstract: Centers who adopted a regional shock protocol emphasizing the delivery of early MCS with invasive hemodynamic monitoring can achieve rapid door to support times and can improve survival in patients who present with AMICS. Larger national studies will be needed to further validate this pilot feasibility study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
135
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(147 citation statements)
references
References 12 publications
(23 reference statements)
2
135
0
10
Order By: Relevance
“…An analysis of the NCDR‐ACTION registry suggested that two of three patients survived the index hospitalization for AMI‐CS . Furthermore, the recent Detroit Cardiogenic Shock Initiative (DCSI) suggested that early use of MCS was associated with a higher survival rate of 76% when compared with previous trials, though this needs to be proven in randomized clinical trials . This may translate into an increasing number of patients with greater burden of comorbidities that are more likely to survive an index hospitalization for PCI in AMI‐CS.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the NCDR‐ACTION registry suggested that two of three patients survived the index hospitalization for AMI‐CS . Furthermore, the recent Detroit Cardiogenic Shock Initiative (DCSI) suggested that early use of MCS was associated with a higher survival rate of 76% when compared with previous trials, though this needs to be proven in randomized clinical trials . This may translate into an increasing number of patients with greater burden of comorbidities that are more likely to survive an index hospitalization for PCI in AMI‐CS.…”
Section: Discussionmentioning
confidence: 99%
“…These devices are a valuable tool in the management of CS due to their ability to maintain vital organ perfusion, decrease LV wall stress and myocardial oxygen consumption, thereby enhancing the likelihood of ventricular recovery . In fact, multiple studies have demonstrated that early initiation of Impella support within 90 minutes of CS onset was associated with higher survival . An additional advantage of early Impella use in CS is the decrease in the use of inotropic agents, thus, reducing the effects of these cardiotoxic drugs .…”
Section: Discussionmentioning
confidence: 99%
“…6,29 In fact, multiple studies have demonstrated that early initiation of Impella support within 90 minutes of CS onset was associated with higher survival. [30][31][32] An additional advantage of early Impella use in CS is the decrease in the use of inotropic agents, thus, reducing the effects of these cardiotoxic drugs. 33 In comparison to the growing evidence base of benefits of the Impella support in CS due to myocardial infarct, very few reports exist on the use of Impella in CS due to PPCM.…”
Section: Discussionmentioning
confidence: 99%
“…A recent United States population‐based observational study found an increasing use of Impella in the last decade for AMI‐related cardiogenic shock . The Detroit Cardiogenic Shock Initiative evaluated the outcomes of Impella in a cohort of 41 patients with AMI complicated by cardiogenic shock . Rapid early delivery of Impella temporary mechanical circulatory support (prior to PCI in 66% of the cases) allowed for immediate hemodynamic stabilization and effective percutaneous myocardial revascularization leading to an overall 76% survival to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%